Decoding Cyberfeminism: Analyzing Representation in the Digital Space through the Instagram Account @womensmarchjkt - Wilmanda, Gesilia; Hariyanti, Nunik (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Feminism, as a social movement committed to fighting for gender equality, has undergone substantial adaptation in interacting with the digital era. The development of information and communication technology has facilitated the presence of the cyberfeminism movement. Cyberfeminism offers a critical perspective by combining the essence of feminism and the potential of technology to fight for gender equality and give voice to marginalized groups. This research examines how the Instagram account @womensmarchjkt, which hosts feminist demonstrations in public spaces based in Jakarta, optimizes Instagram features to promote gender equality in digital spaces. Through this research, we will examine in more depth how the Instagram account @womensmarchjkt applies concepts that represent the cyberfeminism movement. This research uses a qualitative content analysis method to obtain a description of the content and substantial matters from the Instagram account @womensmarchjkt, which includes content, feeds, reels, and highlights from May to July 2023. Data collection techniques through literature studies were used to obtain the data. Secondary theoretical and conceptual references and using source triangulation validation techniques to reduce bias and strengthen research results. Then, reviewing the representation theory put forward by Stuart Hall, it was found that the Instagram account @womensmarchjkt could be categorized as a representation of the cyberfeminism movement. The @womensmarchjkt account not only voices women's issues but also creates a discussion forum and positive mutual interaction. The Instagram account @womensmarchjkt actively educates audiences regarding issues of women and marginalized groups and creates space to share experiences and support each other Keywords: Cyberfeminism; digital space; Instagram @womensmarchjkt; representation.